Potential honey bee (Apis mellifera) allergens associated with IgE-mediated allergy- An In-silico study: In-silico study of honey bee allergens - Anwar, Sadaf; Kausar, Mohd Adnan; Abdalaziz, Halah Salah Mohammed; Elagib, Halima Mustafa; Moawadh, Mamdoh S.; Singh, Rajeev; Thakur, Lovnish; Kar, Subhabrata; Najm, Mohammad Zeeshsan; Saeed, Mohd; Alrobah, Fawaz Ahmed; AlRashidi, Abdullah Nashmi; et al. (Cellular and Molecular Biology, 2023)
Allergies due to honeybee venom (HBV) are reported to be the second most common form of allergy to Hymenoptera venom that occurs after being stung. Indeed, 15–20% of people test IgE positive after being stung. However, accurate data on the incidence of honey bee allergens is missing and estimated to be less than 0.001%. Beekeeping is an ancient and widely practiced activity across the Kingdom of Saudi Arabia. Still, studies on the allergenic effect of the different subspecies of honey bees are very rare in Saudi Arabia. Hence, in this study, using the In-silico approach, we aimed to study and evaluate the effect of allergens from honey bees in Ha’il City, Saudi Arabia on IgE-mediated allergies. A list of potential allergens from Apis mellifera was prepared, and the 3D structure was prepared using the SWISS-MODEL web server and the PDB database was used for retrieving the structure of the immunoglobulin E- fragment antigen-binding (IgE-Fab) region. Molecular docking (clusPro webserver) and molecular dynamics (Schrödinger) results revealed that the B2D0J5 protein from Apis mellifera might be the key protein associated with IgE-mediated allergic response. Overall, the identified knowledge can be used for exploring prophylactic vaccine candidates and improving the diagnosis of allergic reactions to honey bees in the Ha’il region of Saudi Arabia.